Feedback As a New Regulation in Metacognitive Reading Strategies: Review on Metacognitive Regulation - R, Nurmy A.; Yassi, Abdul Hakim; ., Nasmilah; Sahib, Harlinah (International Journal of Membrane Science and Technology, 2023)
Reading is an activity that requires time and persistence, so it needs certain strategies to avoid boredom. Even though it is not a new thing in reading activity, some articles show that Metacognitive Reading Strategies are still relevant nowadays as one of the strategies used to gain students’ comprehension in reading. In MRS, feedback has a significant influence on students’ comprehension. However, feedback is a dependent factor because it can exist in every step of MRS (in planning, monitoring, and evaluating regulations). This is initial research on the position of feedback as a new regulation in MRS after evaluating step. The data were taken from a literature review which reveals metacognitive regulation and how feedback affects the student’s reading comprehension.